STUDI KOMPARATIF TENTANG ZINA DALAM HUKUM INDONESIA DAN HUKUM TURKI - Dian Andriasari (Fakultas Hukum, Universitas Islam Bandung, 2011)
Indonesia and Turkey is a country that has a different ideological and the different legal systems. Adultery in Indonesia is a criminal law, there is a basis legal on Article 284 Criminal Code, the Article occur if one of the subject has been married, so that if both of the subject have not married then would not be a criminal. In Turkey, adultery is not a criminal because of the secular ideologies. They see that sexual intercourse is private, it could be reason for obtained divorces but for the subject who single the adultery has no risk or impact.